Working-Class Men's Constructions of Help-Seeking When Feeling Depressed or Sad. Issue 3 (12th May 2019) - Mahalik, James R.; Dagirmanjian, Faedra R.
In this study, we conducted interviews with 12 working-class men employed in industrial and manual labor to identify their constructions of help-seeking in response to feeling depressed or sad. The semistructured interview format explored participant men's understanding and reactions to depression or sadness, their experiences of depression and reluctance to seek help, and their own and others' reactions to seeking help for feeling depressed or sad. Utilizing the consensual qualitative research methodology, four domains emerged: Concern About Threat and Stigma, Being a Man Means Not Seeking Help, Experiences of Safety and Relief, and Conditions That Reduce Threat and Stigma . The results suggest the need to account for men's experiences of both negative influences (e.g., masculinity injunctions, stigma, and threat to manhood status), as well as adaptive influences (e.g., contexts that reduce stigma) when addressing men's help-seeking for depression and sadness. The domains are illustrative of several theoretical frameworks including social-psychological models of social norms and stigma, precarious manhood theory, inclusive masculinity theory, as well as convergence with other research examining working-class men. Implications are discussed for outreach and practice addressing men's depression and help-seeking.